Ohne Titel (The Pre-Death Bequest of Gerd Spittler, 1984)
Olympus OM2, Kodachrome 64
Keywords: Photography; Anthropology; Tuaregs; Jewelry; Photographs; Silberschmuck; Halskette; Pendant; Kreuz von Agadès; Sammlung Gerd Spittler